Social media as a proxy for intellectual capital: Twitter posts in the cryptocurrency market. (8th April 2022) - Gunay, Samet; Dzenopoljac, Vladimir; Bontis, Nick
This paper investigates the interaction of public information arrivals and volatility in the cryptocurrency market from the perspective of intellectual capital, specifically, relational capital. The empirical analysis was conducted using Kapetanios' unit root test, various scaling (Hurst exponent) tests, a fractionally integrated generalised autoregressive conditionally heteroskedastic model, and Markov regime-switching regression for different series, including the logarithmic returns and abnormal returns, of price and volume series. Following modelling volatility and the derivation of conditional variance, Twitter posts were employed as an independent variable over each series. The results indicate that, while public information arrivals have a positive impact on the volatility of Ripple returns, they cannot divert away the variability of the volume.